Internal factors that are influencing in determining the selction of expertise programs in vocational high school - Dwi Rahdiyanta; Khusni Syauqi; Achmad Arifin (Jurnal Pendidikan Vokasi, 2022)
This study aims to examine the effect of students' internal factors (information literacy, self-understanding, and attitude) on their decision to enroll in a vocational high school mechanical engineering program. It is ex-post facto correlation research using a sample of 300 out of 1,086 students. The sample was established using the proportional random sampling technique using the Krejcie and Morgan formula. The data were collected using questionnaires, observation sheets, and documents. The findings reveal that (1) there is a significant and positive correlation between the internal factors and the student's decision to enroll in the mechanical engineering program of vocational high school (VHS); (2) all internal factors have a significant effect on both directly and indirectly on the student's preference for mechanical engineering program of VHS.